KOHERENSI DALAM PIDATO DONALD TRUMP: SUATU ANALISIS WACANA - MONTOLALU, ANDINO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This skripsi was made as requirement to obtain bachelor Degree in English in Sam Ratulangi University. This research is entitled Coherence of Donald Trump‟s speeches. It is an attempt to analyze and explain the items of coherence. The objectives of this research is to classify, and analyze the items of coherence of Donald Trump‟s speeches. There are three steps to finish this research. First step is preparation, the writer finds 4 speeches among others 1) Victory Speech of Donald Trump, 2) Donald Trump‟s Speech on National Security in Philadelphia, 3) Donald Trump Gives First Campaign Speech Since Hiring Bannon & Conway , and 4) Donald Trump Law & Order Speech. Second step The writer reads it several times and gains an understanding of speeches and identify aspects of coherence that exist in the 4 speeches in according to the theory of Alba-Juez (2009), then classifies the speeches that have been identified in this aspect of coherence. Third step the writer analyzes the data that has been collected and identified according to the theory of Alba-Juez (2009) on discourse analysis. The theory consist of two aspect, they are: mark Coherence and unmark coherence The writer conducts this research by using descriptive method. The data were taken from the Speeches of Donald Trump and analyzed base on Juez‟ (2009). The finding show that there are 261 marked coherence ( 171 examples of addition, 23 examples of contrast, 11 examples of casuality, 15 examples of condition, 14 examples of conclusion, 7 examples of tempo, 9 examples of intensity, 2 examples of comparison, 9 examples of validation ) but there is no marked coherence on instrument and similiaritas. In addition unmarked coherence is not found in the data. Keywords : Discourse Analysis, Speech of Donald Trump., Coherence Items